Resilience as a Mediator of the Relationship Between Forgiveness and Happiness Among College Students - Nahdhata Jaufalaily; Fathul Himam (ANIMA Indonesian Psychological Journal, 2017)
The aim of this study was to examine the relationship between dispositional forgiveness and happiness with a particular focus on the mediating role of resilience. Participants consisted of 203 undergraduate students from a private university in Indonesia who completed the Subjective Happiness Scale (SHS), Heartland Forgiveness Scale (HFS), and Connor-Davidson Resilience Scale (CD-RISC). Results of mediational analysis showed that resilience partially mediated the relationship between forgiveness and happiness with the overall model explaining 27% of the variance in happiness. Limitations and practical implications were discussed.